Assessment of basic education: a comparison among BRAC, formal and never schooled children - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2020)
This report aims to compare the level of basic education of the learners of non-formal schools of BRAC, formal schools and never schooled children. Data were collected from five areas where a surveillance system was in operation. A sample of 720 children, equally distributed by study groups and sex, were randomly selected. This study reveals that NFPE graduates were more likely to have better level of basic education compared to their peers in formal schools. None of the never schooled children had basic education. Neither the formal nor the non-formal system could reach the WCEFA goal to achieve an 80% level of basic education.